Endometrial stromal sarcoma: a rare form of undifferentiated endometrial cancer - Mehra, Dolly; Saiyyed, Anjum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Uterine sarcomas are a rare for of uterine cancers. They account for 0.2% of uterine cancers. The median age group is 40 to 60 years. They run an indolent course. About 60% women recur after a long period. Metastasis may occur even after 20 years. They can be classified into low grade, high grade and undifferentiated types. Low grade ESS has good prognosis. Surgery with adjuvant hormonal therapy is the mainstay of treatment. Adjuvant radiotherapy and chemotherapy have no role in management. The role of lymphadenectomy is not clear. The first line treatment for recurrence is a repeat surgery. Patients require a long term follow up to detect recurrence. Here we present a case of perimenopausal women presenting as a case of AUB. MRI initially diagnosed it as a case of fibroid. Patient underwent TAH with BSO. Subsequent hispathology and immunohistochemistry revealed it to be Low grade ESS. Although rare, endometrial stromal sarcoma should be considered as a differential diagnosis in perimenopausal and postmenopausal women presenting as AUB.